THE ROLE OF VIRTUAL REALITY (VR) IN IMPROVING SPEAKING SKILLS OF SECONDARY SCHOOL STUDENTS - Iskandarova Dilfuza (Western European Studies, 2024)
Recent advancements in technology, particularly Virtual Reality (VR), are revolutionizing the way we learn languages by providing immersive and interactive experiences that engage students in ways that traditional methods cannot. Speaking is a primary language skill, which needs to be developed before the other language skills. Virtual reality technology has shown promise in improving high school students' speaking skills by creating immersive language practice environments. By using VR headsets and interactive tools, students can engage in realistic conversations, presentations, and scenarios to enhance their fluency, pronunciation, and confidence in speaking a foreign language.
Keywords: advancements; realistic; presentations